PENETAPAN TERSANGKA PELAKU TINDAK PIDANA PENCABULAN DALAM BENTUK SODOMI TERHADAP ANAK OLEH PENYIDIK KEPOLISIAN RESOR PARIAMAN - Muhammad Arvi; Susi Delmiati (LPPM Universitas Ekasakti Padang, 2023)
Recently there have been many criminal cases where the victims were not only adults but had reached teenagers, children, and even toddlers. One of the crimes that is being hotly discussed in our society today is crimes against decency such as rape and obscenity (sodomy) of minors. This research is analytical descriptive research. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. The data used in this research are secondary data and primary data. All data and materials obtained from the results of the research were compiled and analyzed qualitatively, and presented in a qualitative descriptive form.